Analytical Techniques for Analyzing Thermally Degraded Monoethylene Glycol with Methyl Diethanolamine and Film Formation Corrosion Inhibitor - AlHarooni, K.; Pack, D.; Iglauer, S.; Gubner, R.; Ghodkay, V.; Barifcani, Ahmed (American Chemical Society, 2016)
Gas hydrate formation and corrosion within gas pipelines are two major flow assurance problems. Various chemical inhibitors are used to overcome these problems, such as monoethylene glycol (MEG) for gas hydrate control and methyl diethanolamine (MDEA) and film formation corrosion inhibitor (FFCI) for corrosion control. As an economical solution, MEG is regenerated due to the large volume required in the field. MEG regeneration involves thermal exposure by traditional distillation to purify the MEG. During this process, MEG is subjected to thermal exposure and so might be degraded. This study focuses on evaluating six analytical techniques for analyzing the degradation level of various MEG solutions consisting of MDEA and FFCI that were thermally exposed to 135 °C, 165 °C, 185 °C, and 200 °C. The analytical techniques evaluated are pH measurement, electrical conductivity, change in physical characteristics, ion chromatography (IC), high performance liquid chromatography–mass spectroscopy (HPLC-MS), and gas hydrate inhibition performance (using 20 wt % MEG solutions with methane gas at pressure from 50 to 300 bar). Most of the analytical techniques showed good capability, while electrical conductivity showed a poor result for solution without MDEA and IC showed poor results for solution exposed to 135 and 165 °C. The primary aim of this paper is thus to provide the industry with a realistic evaluation of various analytical techniques for the evaluation of degraded MEG solutions and to draw attention to the impact of degraded MEG on gas hydrate and corrosion inhibition as a result of the lack of quality control.